ANTHELMINTIC ACTIVITY OF Cuminum cyminum, FOENICULUM VULGARE AND Eugenia caryophyllusAGAINST Pheritima posthuma - Satish Kumar; Kamal Kumar Goyal; Syed Bilal (Indonesian Journal of Pharmacy, 2012)
Ethanol  extract  of  fruit  of Cuminum  cyminum (EECC), aqueous  extract  of  fruit  of Cuminum  cyminum (AECC),  Ethanol extract  of  fruit  of  Foeniculum  vulgare (EEFV), aqueous  extract  of fruit of Foeniculum vulgare (AEFV) and Ethanol extract of flowering bud  of  Eugenia  caryophyllus(  EEEC),  aqueous  extract  of  flowering bud  of Eugenia  caryophyllus(  AEEC) were  taken  up  for  in  vitro studies  on  the  Anthelmintic  activity  against Pheritima  posthuma. Different  concentrations  (25,  50,  100,  200mg/mL)  were  used  for the activity is compared with the reference standard Albendazole at concentration 20mg/mL and normal saline( 0.9% NaCl) was used in control  treatment.  The  results  were  expressed  in  terms  of  time  in minutes  to  report  the  time  of  paralysis  and  time  of  death  of  the earth  worms.  The  results  obtained  from  study  indicate  towards anthelmintic  activity,  supporting  folk  used  of  all  three  plants compared with reference standard. The result established that EEEC and AEEC is more potent as compared with EECC, AECC and EEFV, AEFV.Key  words:  Anthelmintic  activity,  Cuminum  cyminum,  Eugenia caryophyllus, Foeniculum vulgare, Pheritima posthuma.